Dos nuevas especies de Hyla (Amphibia: Anura) de Colombia, con aportes al conocimiento de Hyla Bogotensis Dos nuevas especies de Hyla (Amphibia: Anura) de Colombia, con aportes al conocimiento de Hyla Bogotensis - Ruiz C. Pedro M.; Lynch John D. (Caldasia)
In this contribution previously unpublished information about the geographic variation in Hyla bogotensis (W. Peters) and the tadpole characters is given. Hyloscirtus vermiculatus B. Lutz & Ruiz-C. is regarded as a synonym. The taxonomic status of Hyla platydactyla is discussed and is concluded that it might prove to be not separable from H. bogotensis. New records for H. denticulenta and H. phyllognatha are provided together with descriptive notes.  A new species of the H. bogotensis group, H. piceigularis, from the cloud fotest belt of the Departamento de Santander in the Eastern Andes of Colombia, is described based on adults and tadpoles.  In addition another new species, H. sarampiona , closely related to H. larinopygion Duellman and H. lindae Duellman & Altig is named from the Pargue Nacional Natural de Munchique in the cloud forest belt of the Western Andes of Colombia. In this contribution previously unpublished information about the geographic variation in Hyla bogotensis (W. Peters) and the tadpole characters is given. Hyloscirtus vermiculatus B. Lutz & Ruiz-C. is regarded as a synonym. The taxonomic status of Hyla platydactyla is discussed and is concluded that it might prove to be not separable from H. bogotensis. New records for H. denticulenta and H. phyllognatha are provided together with descriptive notes.  A new species of the H. bogotensis group, H. piceigularis, from the cloud fotest belt of the Departamento de Santander in the Eastern Andes of Colombia, is described based on adults and tadpoles.  In addition another new species, H. sarampiona , closely related to H. larinopygion Duellman and H. lindae Duellman & Altig is named from the Pargue Nacional Natural de Munchique in the cloud forest belt of the Western Andes of Colombia.